Pengaruh Endorphin Massage terhadap Kelancaran Produksi ASI pada Ibu Post Partum di RSUD Ratu Aji Putri Botung: Effect of Endorphin Massage on Smooth Milk Productionto A Post Partum Mother at Ratu Aji Putri Botung Hospital - Rini Septianasari; Moneca Diah Listiyaningsih (Journal of Holistics and Health Sciences, 2024)
Coverage of exclusive breastfeeding in Penajam Paser Utara district in 2021 is 31.8% of the target of 75%, so coverage of exclusive breastfeeding has not been met. not enough. One of the non-pharmacological treatments to increase breast milk is by doing endorphin massage to increase milk production so as to provide the comfort and relaxation that postpartum mothers really need.To determine the effect of endorphin massage on the smooth production of breast milk in post partum mothers at Ratu Aji Putri Botung Hospital. This study used a type of quantitative research method with a pre-experimental approach, namely one group pretest-posttest design. The population in this study were all post partum mothers as many as 30 respondents in June. The sample in this study was part of the total population of 15 respondents post partum mothers 2 days that meet predetermined criteria. The sampling technique used purposive sampling. Observation sheet data collection instrument, statistical test used Wilcoxon Matched Pairs Sign Test. Based on the results of statistical tests using the Wilcoxon test that the p-value is 0.000 and 0.001 or less than 0.05 which means that the p-value < α. So it can be concluded that there is an effect of endorphin massage on the smooth production of breast milk in post partum mothers at Ratu Aji Putri Botung Hospital. The conclusion from this study is that there is an effect of Endorphin Massage on the smooth production of breast milk because there is a significant difference between the smooth production of breast milk before and after treatment.   ABSTRAK Cakupan ASI Esklusif di kabupaten Penajam Paser Utara pada  tahun 2021 sebesar 31,8% dari target 75 % sehingga cakupan ASI Esklusif belum tepenuhi.Penyebab kegagalan pemberian ASI esklusif tersebut adalah masalah yang dialami ibu post partum dalam produksi asi salah satunya sindrom asi kurang. Penanganan non farmakologis untuk memperbanyak ASI salah satunya adalah dengan melakukan endorphin massage untuk meningkatkan produksi ASI sehingga memberikan kenyamanan dan relaksasi yang sangat dibutuhkan ibu nifas. Untuk mengetahui pengaruh endorphin massage terhadap kelancaran produksi ASI pada ibu post partum di RSUD Ratu Aji Putri Botung. Penelitian ini menggunakan jenis metode penelitian kuantitatif dengan pendekatan pre eksperimen yaitu one group pretest-posttest design.Populasi dalam penelitian ini adalah seluruh ibu post partum sebanyak 30 responden pada bulan Juni.Sampel pada penelitian ini sebagian dari jumlah populasi 15 responden ibu post partum 2 hari yang memenuhi kriteria yang telah ditetapkan.Teknik pengambilan sampel menggunakan purposivesampling. Instrumen pengumpulan data lembar observasi,uji statistic yang digunakan Wilcoxon Matched Pairs Sign Test. Berdasarkan hasil uji statistic menggunakan ujiWilcoxon bahwa p-value 0,000 dan 0.001 atau kurang dari 0.05 yang berarti bahwa p-value< α. Sehinggadapatdisimpulkan ada pengaruh endorphin massage terhadap kelancaran produksi ASI pada ibupostpartumdi RSUD Ratu Aji Putri Botung. Kesimpulan dari penelitian ini adalahAda pengaruh Endorphin Massage terhadap kelancaran produksi ASI karena ada perbedaan yang signifikan antara kelancaran produksi ASI sebelum dan sesudah perlakuan.